Roles of biological and physical processes in driving seasonal air–sea CO2 flux in the Southern Ocean: New insights from CARIOCA pCO2 - Merlivat, L.; Boutin, J.; Antoine, David (Elsevier, 2014)
On a mean annual basis, the Southern Ocean is a sink for atmospheric CO2. However the seasonality of the air–sea CO2 flux in this region is poorly documented. We investigate processes regulating air–sea CO2 flux in a large area of the Southern Ocean (38°S–55°S, 60°W–60°E) that represents nearly one third of the subantarctic zone. A seasonal budget of CO2 partial pressure, pCO2 and of dissolved inorganic carbon, DIC in the mixed layer is assessed by quantifying the impacts of biology, physics and thermodynamical effect on seawater pCO2. A focus is made on the quantification at a monthly scale of the biological consumption as it is the dominant process removing carbon from surface waters. In situ biological carbon production rates are estimated from high frequency estimates of DIC along the trajectories of CARIOCA drifters in the Atlantic and Indian sector of the Southern Ocean during four spring–summer seasons over the 2006–2009 period.Net community production (NCP) integrated over the mixed layer is derived from the daily change of DIC, and mixed layer depth estimated from Argo profiles. Eleven values of NCP are estimated and range from 30 to 130 mmol C m− 2 d− 1. They are used as a constraint for validating satellite net primary production (NPP). A satellite data-based global model is used to compute depth integrated net primary production, NPP, for the same periods along the trajectories of the buoys. Realistic NCP/NPP ratios are obtained under the condition that the SeaWiFS chlorophyll are corrected by a factor of ≈ 2–3, which is an underestimation previously reported for the Southern Ocean.Monthly satellite based NPP are computed over the 38°S–55°S, 60°W–60°E area. pCO2 derived from these NPP combined with an export ratio, and taking into account the impact of physics and thermodynamics is in good agreement with the pCO2 seasonal climatology of Takahashi (2009). On an annual timescale, mean NCP values, 4.4 to 4.9 mol C m− 2 yr− 1 are ≈ 4–5 times greater than air–sea CO2 invasion, 1.0 mol C m− 2 yr− 1. Our study based on in situ and satellite observations provides a quantitative estimate of both seasonal and mean annual uptake of CO2 in the subantarctic zone of the Southern Ocean. These results bring important constraints for ocean circulation and biogeochemical models investigating future changes in the Southern Ocean CO2 fluxes.